Transformation of Muaro Labuah Market Into Green Open Space (Rth) and its Impact on The Economy of Muaro Labuah Community in 2012-2023 - Nengsih, Yosi Putri; Erawati, Meri; Junaidi, Juliandry Kurniawan (MSJ : Majority Science Journal, 2024)
This study discusses the history and impact of the conversion of the Muaro Labuah market into a Green Open Space (RTH) and its impact on the economy of the Muaro Labuah community in 2012-2023. The purpose of this study is to describe the background of the conversion of the Muaro Labuah market in 2012-2023 and to describe the impact on the economy of the Muaro Labuah community after the conversion of the Muaro Labuah market into a Green Open Space (2012-2023). The research method used in this study is the Historical Research Method. The results of this study indicate that the background of the conversion of the Muaro Labuah Market is due to the limited land area of ​​only 1 hectare, so that the market conditions feel crowded, especially on market days (Monday-Thursday) where the number of visitors increases quite significantly. And with limited land, traders have to jostle to get a place to trade. In addition, the relocation of the market is also due to the Muaro Labuah Market often experiencing congestion because this market is located on the edge of the Muaro Labuah Padang intersection. The economic impact experienced by Muaro Labuah Lama traders and relocated traders after the conversion of the Muaro Labuah market into a Green Open Space 2012-2023 is a fairly drastic decrease in income, where the average decrease in income reached 50% since the market was relocated. So it can be concluded that the conversion of the Muaro Labuah Market into a Green Open Space occurred due to limited space/location and its impact on the economy of the Muaro Labuah community in 2012-2023 generally had an impact on traders' income.